TLR2 and endosomal TLR-mediated secretion of IL-10 and immune suppression in response to phagosome-confined Listeria monocytogenes. - Brittney N Nguyen; Alfredo Chávez-Arroyo; Mandy I Cheng; Maria Krasilnikov; Alexander Louie; Daniel A Portnoy (PLoS Pathogens)
Listeria monocytogenes is a facultative intracellular bacterial pathogen that escapes from phagosomes and induces a robust adaptive immune response in mice, while mutants unable to escape phagosomes fail to induce a robust adaptive immune response and suppress the immunity to wildtype bacteria when co-administered. The capacity to suppress immunity can be reversed by blocking IL-10. In this study, we sought to understand the host receptors that lead to secretion of IL-10 in response to phagosome-confined L. monocytogenes (Δhly), with the ultimate goal of generating strains that fail to induce IL-10. We conducted a transposon screen to identify Δhly L. monocytogenes mutants that induced significantly more or less IL-10 secretion in bone marrow-derived macrophages (BMMs). A transposon insertion in lgt, which encodes phosphatidylglycerol-prolipoprotein diacylglyceryl transferase and is essential for the formation of lipoproteins, induced significantly reduced IL-10 secretion. Mutants with transposon insertions in pgdA and oatA, which encode peptidoglycan N-acetylglucosamine deacetylase and O-acetyltransferase, are sensitive to lysozyme and induced enhanced IL-10 secretion. A ΔhlyΔpgdAΔoatA strain was killed in BMMs and induced enhanced IL-10 secretion that was dependent on Unc93b1, a trafficking molecule required for signaling of nucleic acid-sensing TLRs. These data revealed that nucleic acids released by bacteriolysis triggered endosomal TLR-mediated IL-10 secretion. Secretion of IL-10 in response to infection with the parental strain was mostly TLR2-dependent, while IL-10 secretion in response to lysozyme-sensitive strains was dependent on TLR2 and Unc93b1. In mice, the IL-10 response to vacuole-confined L. monocytogenes was also dependent on TLR2 and Unc93b1. Co-administration of Δhly and ΔactA resulted in suppressed immunity in WT mice, but not in mice with mutations in Unc93b1. These data revealed that secretion of IL-10 in response to L. monocytogenes infection in vitro is mostly TLR2-dependent and immune suppression by phagosome-confined bacteria in vivo is mostly dependent on endosomal TLRs.